IMPLEMENTASI MANAJEMEN KELAS DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Irma Rosita; Putri Wahyuni (Jurnal Tarbiyah Almuslim, 2023)
This research aims to find out the role of the principal in improving teacher discipline at SMAS Tauthiah Arongan. This research uses a field research approach. The nature of this research is qualitative descriptive research. In the data collection process, researchers used observation, interviews and documentation methods found at SMAS Tauthiah Arongan. Research findings inform: That the principal as a leader balances various tasks such as leader, manager, supervisor. The principal's main role is to build leadership capacity in the school in creating and maintaining study groups and the principal must also set an example that can be imitated by teachers, staff and students. The existing discipline is also good, teachers who are late in teaching are certainly given a personal approach and coaching. Apart from that, the evaluation provided is in the form of coaching so that this can be a focus to further improve discipline. Meanwhile, the punishment given when teachers or employees violate existing rules is gradual coaching.